A közjó és az önérdek konfliktusa - avagy a pillanatnyi haszon mint társadalmi csapda - Fodor, Tímea (Kultúratudományi Szemle, 2022)
The conflict between the public good and self-interest - or momentary gain as a social trap Tímea Fodor Based ont he book of Garret Hardin, The Tragedy of the Commons I analyze the human nature’s functioning in the public sphere. I ask the quetion, how it is possible that humans see the long term damages of their activities but they do not offer they actual profit for a better future.